2015
DOI: 10.1073/pnas.1420588112
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fusion during phage lysis

Abstract: In general, phages cause lysis of the bacterial host to effect release of the progeny virions. Until recently, it was thought that degradation of the peptidoglycan (PG) was necessary and sufficient for osmotic bursting of the cell. Recently, we have shown that in Gram-negative hosts, phage lysis also requires the disruption of the outer membrane (OM). This is accomplished by spanins, which are phage-encoded proteins that connect the cytoplasmic membrane (inner membrane, IM) and the OM. The mechanism by which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 43 publications
2
74
0
Order By: Relevance
“…The PG meshwork acts as a negative inhibitor of gp11 function. Previously, we showed that PG depletion in the presence of physiological levels of Rz-Rz1 resulted in lysis, independent of holin or endolysin function (8). This implied the intact PG network acts a negative regulator of two-component spanin function, preventing IM-OM fusion until the lytic pathway is initiated by holin triggering (8).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The PG meshwork acts as a negative inhibitor of gp11 function. Previously, we showed that PG depletion in the presence of physiological levels of Rz-Rz1 resulted in lysis, independent of holin or endolysin function (8). This implied the intact PG network acts a negative regulator of two-component spanin function, preventing IM-OM fusion until the lytic pathway is initiated by holin triggering (8).…”
Section: Resultsmentioning
confidence: 88%
“…Proposed structural models of these complexes rely heavily on detailed genetic and biochemical analysis (4-7), focused on the predominantly alpha-helical, coiled-coil structure of the i-spanin. Moreover, there is compelling evidence that the spanin complexes disrupt the OM by causing IM-OM fusion and that this topological function is blocked as long as the PG is intact (8).…”
mentioning
confidence: 99%
“…Phages infecting Gram-negative bacteria harbour an additional lytic tool; the spanins. Two-component spanins are integral membrane proteins (i-spanins and o-spanins for inner and outer membranes, respectively) that form a complex spanning the periplasm, and recently also unimolecular spanins (u-spanins) have been described (Summer et al, 2007;Rajaure et al, 2015). At the time of lysis, spanins change their conformation to fuse the outer and inner membranes.…”
Section: Proteins Diversity and Domain Architecturesmentioning
confidence: 99%
“…Although the lysis event has been well-studied operationally through the use of video-microscopic as well as molecular and physiological methods 9–11 , there is little information on the impact of the lytic pathway on biomechanics and physical structure of the infected cell. During the last decade, several researchers have used atomic force microscopes (AFM) to characterize the infection cycle of E. coli by different phages.…”
Section: Introductionmentioning
confidence: 99%